Implementation of Loss Assessment Theory in Improving the Effectiveness of the Connexity Justice System - Savira Rahmadhani; Mohamad Tohari; Naya Amin Zaini (Journal of Management Economic and Financial, 2024)
This research discusses the dynamics and challenges in legal regulation related to human trafficking with a focus on refugees in Indonesia. Although Indonesia is a significant transit country for refugees, the existing legal framework, particularly Law No. 6 of 2011 on Immigration, does not specifically regulate the status and protection of refugees. Consequently, refugees are often viewed as illegal immigrants, leading to human rights violations and legal uncertainties. The first subtitle conducts an analysis of how dynamic legal regulations interact with the challenges faced in human trafficking. It further explores the necessary efforts to create legal certainty, including the need for more specific regulations and transparent procedures. This research is expected to contribute to the development of better policies and practices in handling human trafficking cases and protecting the rights of refugees in Indonesia